Transcriptomic Analysis of Steinernema Nematodes Highlights Metabolic Costs Associated to Xenorhabdus Endosymbiont Association and Rearing Conditions - Lefoulon, Emilie; McMullen, John G.; Stock, S. Patricia (Frontiers in Physiology, 2022)
Entomopathogenic nematodes of the genus Steinernema have a mutualistic relationship with bacteria of the genus Xenorhabdus and together they form an antagonist partnership against their insect hosts. The nematodes (third-stage infective juveniles, or IJs) protect the bacteria from the external environmental stressors and vector them from one insect host to another. Xenorhabdus produce secondary metabolites and antimicrobial compounds inside the insect that protect the cadaver from soil saprobes and scavengers. The bacteria also become the nematodes’ food, allowing them to grow and reproduce. Despite these benefits, it is yet unclear what the potential metabolic costs for Steinernema IJs are relative to the maintenance and vectoring of Xenorhabdus. In this study, we performed a comparative dual RNA-seq analysis of IJs of two nematode-bacteria partnerships: Steinernema carpocapsae-Xenorhabdus nematophila and Steinernema. puntauvense-Xenorhbdus bovienii. For each association, three conditions were studied: (1) IJs reared in the insect (in vivo colonized), (2) colonized IJs reared on liver-kidney agar (in vitro colonized), and (3) IJs depleted by the bacteria reared on liver-kidney agar (in vitro aposymbiotic). Our study revealed the downregulation of numerous genes involved in metabolism pathways, such as carbohydrate, amino acid, and lipid metabolism when IJs were reared in vitro, both colonized and without the symbiont. This downregulation appears to impact the longevity pathway, with the involvement of glycogen and trehalose metabolism, as well as arginine metabolism. Additionally, a differential expression of the venom protein known to be secreted by the nematodes was observed when both Steinernema species were depleted of their symbiotic partners. These results suggest Steinernema IJs may have a mechanism to adapt their virulence in absence of their symbionts.